2021
DOI: 10.1111/jsr.13429
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the end of COVID confinement on pandemic dreams, as assessed by a weekly sleep diary: a longitudinal investigation in Italy

Abstract: Summary The Coronavirus 2019 pandemic strongly affected our sleep and dream activity. Many cross‐sectional studies highlighted increased dream recall frequency, and revealed a great presence of pandemic‐related oneiric contents. Here, we present the first prospective study carried out on an Italian sample. One‐hundred subjects were requested to fill out a web‐survey including socio‐demographic information, and questionnaires collecting sleep and clinical measures during lockdown. A final sample of 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
60
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(70 citation statements)
references
References 45 publications
9
60
1
Order By: Relevance
“…As discussed further below, when taken together, these findings are in keeping with the continuity hypothesis of dreaming. 14,15 Very early on, we, and others, argued that some of those reported sleep symptoms (eg vivid dreams) possibly reflected the biological response to the extraordinary stress and uncertainty that the populace was facing. 1,[16][17][18][19] For example, it is known that rapid eye movement (REM) sleep structure, during which most of our dreaming occurs, changes first during chronic stress, and more so than any other measured sleep characteristic.…”
Section: Covid-19 Pandemic and Lockdownmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed further below, when taken together, these findings are in keeping with the continuity hypothesis of dreaming. 14,15 Very early on, we, and others, argued that some of those reported sleep symptoms (eg vivid dreams) possibly reflected the biological response to the extraordinary stress and uncertainty that the populace was facing. 1,[16][17][18][19] For example, it is known that rapid eye movement (REM) sleep structure, during which most of our dreaming occurs, changes first during chronic stress, and more so than any other measured sleep characteristic.…”
Section: Covid-19 Pandemic and Lockdownmentioning
confidence: 99%
“…As discussed further below, when taken together, these findings are in keeping with the continuity hypothesis of dreaming. 14 , 15 …”
Section: Sleep and Neuropsychiatric Complications Of The Covid-19 Pandemic Lockdown Infection And Vaccinationmentioning
confidence: 99%
“…Against this background, a growing number of research papers were showing that the outbreak was associated with relevant psychological symptoms [3,4] and sleep quality was significantly worsened [4][5][6]. Many investigations also explored oneiric activity during the pandemic [7][8][9][10][11][12][13][14][15][16]. Results from different countries revealed higher dream-recall frequency during the pandemic (e.g., [16]).…”
Section: Introductionmentioning
confidence: 99%
“…Just a few studies aimed to understand the stability of the observed changes in dream activity at different pandemic stages. In this respect, Scarpelli et al [14] longitudinally investigated the impact of the easing of restrictions on dreaming during the first week after lockdown. The results showed higher dream recall and lucid-dream frequency during lockdown than post-lockdown [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation